2015
DOI: 10.1534/genetics.115.176628
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Composite Spike Form in Barley and ‘Miracle-Wheat’

Abstract: Inflorescences of the tribe Triticeae, which includes wheat (Triticum sp. L.) and barley (Hordeum vulgare L.) are characterized by sessile spikelets directly borne on the main axis, thus forming a branchless spike. ‘Compositum-Barley’ and tetraploid ‘Miracle-Wheat’ (T. turgidum convar. compositum (L.f.) Filat.) display noncanonical spike-branching in which spikelets are replaced by lateral branch-like structures resembling small-sized secondary spikes. As a result of this branch formation ‘Miracle-Wheat’ produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
166
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 39 publications
7
166
1
1
Order By: Relevance
“…In another type of variation, one or more spikelets are replaced by long lateral branches, which form their own spikelets and florets. Mutations of the WFZP-A/BH t -A1 gene, encoding an AP2/ERF transcription factor, lead to such noncanonical spike branching (Derbyshire and Byrne, 2013;Dobrovolskaya et al, 2015;Poursarebani et al, 2015), which is similar to the branching produced by mutating its orthologs in maize, rice, and Brachypodium distachyon (Chuck et al, 2002;Komatsu et al, 2003). Although these recent breakthroughs shed light on the molecular mechanisms underlying rare supernumerary spikelet variations, little is known about genetic factors affecting the architecture of archetypal wheat spike, its complexity, and grain yield.…”
mentioning
confidence: 99%
“…In another type of variation, one or more spikelets are replaced by long lateral branches, which form their own spikelets and florets. Mutations of the WFZP-A/BH t -A1 gene, encoding an AP2/ERF transcription factor, lead to such noncanonical spike branching (Derbyshire and Byrne, 2013;Dobrovolskaya et al, 2015;Poursarebani et al, 2015), which is similar to the branching produced by mutating its orthologs in maize, rice, and Brachypodium distachyon (Chuck et al, 2002;Komatsu et al, 2003). Although these recent breakthroughs shed light on the molecular mechanisms underlying rare supernumerary spikelet variations, little is known about genetic factors affecting the architecture of archetypal wheat spike, its complexity, and grain yield.…”
mentioning
confidence: 99%
“…The genes controlling barley inflorescence architecture and development have only been revealed for a few characters. Major genes that control row type (vrs1 [Komatsuda et al, 2007], intermedium-c [Ramsay et al, 2011], and vrs4 [Koppolu et al, 2013]), the conversion of awns into an extra floret (Hooded; Müller et al, 1995), adherence of the hull to the caryopsis (nud; Taketa et al, 2008), swelling of lodicules conferring open/ closed flowering (cleistogamy/chasmogamy) and spike density (cly1 [Nair et al, 2010] and zeo1 [Houston et al, 2013]), elongation of awns and pistil morphology (lks2; Yuo et al, 2012), suppression of bracts (trd1; Whipple et al, 2010;Houston et al, 2012), spike branching (com2; Poursarebani et al, 2015), and brittleness of the rachis (btr1/btr2; Pourkheirandish et al, 2015) were recently cloned. A large number of additional morphological mutants that influence barley inflorescence development (Forster et al, 2007) also have been described, and the underlying genes need to be identified to reach a more complete understanding of the regulatory pathways controlling barley spike architecture and development (Forster et al, 2007).…”
mentioning
confidence: 99%
“…Vrs4 has also been found to be involved in another mutant phenotype derived from a particular development of the node. Poursarebani et al [22] demonstrated that vrs4 is involved in the regulation of compositum2 expression, a gene found to be orthologous to the branched head t (bh t ) locus regulating spike-branching in tetraploid 'Miracle-Wheat'. The branching of the spike can have an epigenetic basis.…”
Section: Branched Spikementioning
confidence: 99%